Effect of Work Environment and Work Loads on the Performance of Police Educators in Sepolwan Lemdiklat Polri - Manaf, Abd.; Matin, Matin; Zulaikha, Siti (Universitas Malikussaleh, 2019)
The objective of this causal research was to obtain information concerning: (1) the effect of work environment toward work performance; (2) the effect of workload toward work performance; and (3) the effect of work environment toward workload. The research was conducted using a survey method with a path analysis testing hypothesis. This research, principals of teachers on Police Women School - Polri has been chosen as a unit analysis and 90 samples of principals were selected at random. The results of the research are as follows: (1) there is a direct positive effect of work environment toward work performance; (2) there is a direct negative effect of workload toward work performance; and (3) there is a direct negative effect of work environment toward workload.